25-OH-VitaminD3 level in elite sports: Impact on muscle damage and infections - Erpenbach, K.; Mayer, W.; Hoffmann, U.; Mücke, S. (Swiss Sports & Exercise Medicine, 2020)
Abstract Muscle damage as well as recurrent and serious infections especially to the end of the playing period in team sport or to the end of preparation for competition in endurance or single sport are the most common symptoms in elite sport demolishing optimal training results. Are VitaminD deficiency responsible for these symptoms in elite sport. Methods: In 111 elite athletes (male: 50 - female: 61 / soccer: 21 - field hockey: 62 - olympics: 19 - tennis: 5 - motorsports ‹DTM-Formula 1›: 4) blood vitaminD were determined. In all elite athletes the symptoms muscle damage and infections were correlated. A Spearman-ranking coefficient of correlation, a chi-square-test (?²-Test) by Pearson and an independent t-test were used. p<0,05 was supposed to be significant, p<0,01 highly significant. Results: In 51,3% of all elite athletes (N=57/111) a vitaminD-deficiency (< 30 ng/ml) was established. In cases of young player (< 18) compared to national A player VitaminD significantly were poorly supplied [vitaminD: 25,71 ± 9,58 ng/ml vs. 35,87 ± 12,35 ng/ml (p=0,007)]. Muscle damages (in 73% of all cases) significantly occurred in vitamin D deficiency [29,13 ± 9,38 ng/dl vs. 36,27 ± 12,09 ng/dl, p=0,005] more frequently. Comparing the settings of vitaminD <40 ng/ml vs. > 40ng/ml [27,50 ± 7,85 ng/ml vs. 46,31 ± 6,71 ng/ml, OR=4,53, p=0,007] muscle damage were observed 4,53 times more frequent in the lower group. No significances were observed in infection. Conclusion: Independently to the type of sports deficiency of VitaminD in elite sports was observed. VitaminD play an important and significant role developing muscle damages. Further studies to prevent muscle damages and recurrent infections by treating elite athletes with high-dose VitaminD to eradicate those deficiencies are necessary.